Chromosomal Mapping Technique for Early Diagnosis of Human Genetic Diseases in Libyan populations, is it needed? (Journal of Medical Sciences, 2022)
Recently, there is growing interest in the early diagnosis of various human genetic diseases, with the emergence of the rats of several categories of genetic diseases yearly. The majority of the human genome organize into distinct structures known as chromosomes. Notably, the diagnosis of genetic disorders field clarified that chromosomes altered in their nature contributed to several human genetic diseases. Several studies indicated that the most common chromosomal aberration is aneuploidy, which is an alteration in the number of chromosomes due to an extra or missing chromosome. In line, numerical chromosomal diseases are caused by a complex combination of genetic alteration, behavioral, and environmental factors. Instances of these conditions include down syndrome, and others. Indeed, different chromosomal diseases have different phenotypes, and genotypes. However, similar features and associated diseases may overlap between those disorders, therefore, diagnosis of chromosomal diseases depending on clinical features is not accurate. Thereby, early detection of genetic diseases during (Intrauterine or neonatal life), using a suitable approach such as the chromosomal mapping technique is ideal and required. Additionally, the techniques are the cornerstone of the management of diseases associated with genetic diseases. In a society such as the Libyan population, genetic diseases impact not only physical health but also psychological and social well-being. Therefore, testing for genetic diseases is of great importance for the diagnosis, prognosis, and timely intervention of familial patients and their high-risk relatives. In this paper, our main concern is numerical chromosomal aberrations diseases.  Moreover, sightsees chromosomal mapping techniques as the most suitable approach. Furthermore, clarify how our application of this technique can be the provision of appropriate that accurately detects human genetic diseases for most of the Libyan populations.